Direct Acetophenone–Acetophenone Crossed Aldol Reaction and Aldol Self‐Reaction Promoted by a Tethered Ru–S Complex. Issue 19 (18th May 2018) - Pommerening, Phillip; Stahl, Timo; Oestreich, Martin
Abstract : The serendipitous discovery of aldol reactions of two methyl ketones is reported. The tertiary aldols do form during the dehydrogenative Si–O coupling of the corresponding enolizable ketone and a hydrosilane. The ratio of the expected silyl enol ether and the aldol adduct depends on various reaction parameters but is particularly pronounced with the hydrosilane as the limiting reagent. Aside from aldol self‐reactions, the direct crossed aldol reaction is, in principle, also possible. The hydrosilane can be replaced by a hydroborane, then involving a boron enolate as the enol component. Abstract : The direct crossed aldol reaction of two electronically different acetophenone derivatives occurs during the dehydrogenative Si–O coupling of the more reactive component and the hydrosilane. The key intermediate is the corresponding silyl enol ether or, employing a hydroborane, a boron enolate.